Peran Guru Rupaka Daalam Menanamkan Ajaran Agama Hindu Dalam Keluarga Di Kota Surakarta - Putu Budiadnya (Jayapangus Press, 2019)
The role of Guru Rupaka is very much needed in the process of religious learning. Aside from being a driver for children and youth in learning Hinduism, Guru Rupaka is an example or example for children and youth in everyday life. Therefore, the role of the teacher seems to be very important in its development. Today's era with the characteristics of progress in the field of science and technology, realized or not has shifted the role of Guru Rupaka or parents in providing education to their children. In the past before television was known, the tradition of telling bedtime stories that conveyed moral teachings and religious ethics can still be found, but lately this tradition has increasingly disappeared, even though the role of Guru Rupaka or parents to supplement religious education obtained at formal schools is needed . Realizing that there have been changes in current conditions and situations with unavoidable impacts, the education of Hinduism in the family is very important in order to fortify and develop children's morals. This shows that the role of Guru Rupaka is very important in instilling the teachings of Hindu religion in the family. The role of the Guru Rupaka in instilling the teachings of Hinduism in the family is problematic mapping of various aspects referring to the theory of relativity and electricity which functionally can provide guidance to see the problem in more focus to dissect this problem used theories namely: 1) Educational theory, 2) Convergence Theory. To achieve these objectives, adequate and relevant data is needed. In rigkas the findings obtained are summed up in the following points: 1 The function of religious education in the family is as follows, Planting the value of Hindu religious teachings that can be used as a way of life in achieving prosperity and happiness of life (Moksartham Jagadhita) 2) Guru Rupaka have a very big responsibility in giving direction to the development of the child's soul. Guru Rupaka must provide guidance to children by establishing their first education at home, then sending them to school on time. After the time to get married, Guru Rupaka is obliged to marry off her children. 3) Parents who can give appreciation and receive children in the family can prevent children from behaving aggressively, the integrity of the family makes children feel and understand the direction and guidance of their parents even though they are not physically present in front of him. So parents who are democratic, give awards and praise to their children will prevent children from behaving that are not in accordance with moral values. 4) The purpose of planting Hindu teachings in the family is to create a child who is supernatural and has responsibility and holds fast to the teachings of dharma.